Understanding Village Community Social Interaction in Religious and Community Activities During the Pandemic Crisis in Indonesia: What Evidences Say - Maemunah, Maemunah; Mukramin, Sam'un; Haniah, St. (Jurnal Mamangan, 2022)
This study was to understand rural communities' communication, interaction models, and literacy during the pandemic, especially issues related to social activities and worship in places of community activity. We carry out this study in a descriptive qualitative study. Our data is obtained from more than 100 legal and health science books and journal topics; we selected 50 out of 100 as a sample. We examine the study with a phenomenological approach. Data analysis involves data coding systems, in-depth data analysis, interpreting data, and providing conclusions that can answer problems with high validity. As for the results, we understand that village communities continue to interact and communicate with fellow residents by holding traditional and religious events during the pandemic emergency response period. In other words, the people in the village are undoubtedly aware of the issues and rules in responding to the pandemic. This is different in the model and literacy of its interaction with people in cities where they are ready to respond to pandemic policies. This is because the understanding and contact model of community social interaction in the village developed long before the pandemic response. Therefore, we hope the results of this study will be helpful for similar studies in the future.